Impact of phone call intervention on glycemic control in diabetes patients: a systematic review and meta-analysis of randomized, controlled trials. - Naeti Suksomboon; Nalinee Poolsup; Yuu Lay Nge (PLoS ONE)
Background Telephone-delivered intervention can provide many supports in diabetes self-management to improve glycemic control. Several trials showed that telephone intervention was positively associated with glycemic outcomes in diabetes. The objective of this meta-analysis was to assess the impact of telephone contact intervention (intervention group) on glycemic control compared with standard clinical care (control group). Methods Randomized control studies of telephone intervention in diabetes were searched on Medline (Pubmed), the Cochrane Central Register of Controlled Trials, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Web of Science (ISI), and Scopus. Electronic search was done from inception to April 2013. The following MeSH terms were used: diabetes mellitus, randomized control trials and telemedicine, together with keywords including phone intervention, diabetes, and glycemic control. Historical search was also conducted on the references of relevant articles. The quality of the trials was assessed using Maastricht-Amsterdam scale. Treatment effect was estimated with mean difference in the change of hemoglobin A1c (HbA1c) from baseline between the intervention and control groups. Results A total of 203 articles were examined. Five trials involving 953 patients met the inclusion criteria and contributed to the meta-analysis. Telephone contact intervention was no more effective than standard clinical care in improving glycemic control (pooled mean difference in HbA1c -0.38%, 95%CI -0.91 to 0.16%). Conclusions This meta-analysis showed that the phone contact intervention was no more effective than standard clinical care in improving glycemic control in diabetes. However, telephone intervention may still have potential benefits especially for low-and middle-income countries; thus further large sample size and well-controlled studies are needed to evaluate the impact of the intervention.